Experiences and difficulties of primiparous women in breastfeeding (Research, Society and Development, 2022)
Introduction: breastfeeding is one of the best modality of infant nutrition exclusively up to the sixth month of life of the baby and complemented from this age, however, breastfeeding is a complex process that requires specific care. Objective: to understand the difficulties and experiences of primiparous mothers in relation to the breastfeeding process. Methodology: this is a descriptive study with a qualitative approach conducted with seven women who were breastfeeding for the first time and were accompanied by family health teams from a municipality located in the north of Minas Gerais. Results: the results related to the breastfeeding phenomenon were presented: "Experiences and difficulties to breastfeed" and their categories: "He had a lot of difficulty getting the breast", "For him to grow healthy" and "The doctor guided me on the importance of milk". Throughout the experience, women face periods of uncertainty and doubts, demanding new attitudes and confrontation with the unknown. Conclusion: health professionals, specifically nursing professionals, have sometimes remained the margin of work with these women. It is necessary to guide and support them, particularly in facing periods of difficulties and doubts, with the aim of attenuating and even resonating them.